Wet Laws, Drinking Establishments, and Violent Crime - D. Mark Anderson; Benjamin Crost; Daniel I. Rees (Institute for the Study of Labor (IZA), 2014)
Drawing on county-level data from Kansas for the period 1977-2011, we examine whether plausibly exogenous increases in the number of establishments licensed to sell alcohol by the drink are related to violent crime. During this period, 86 out of 105 counties in Kansas voted to legalize the sale of alcohol to the general public for on-premises consumption. We provide evidence that these counties experienced substantial increases in the total number of establishments with on-premises liquor licenses (e.g., bars and restaurants). Using legalization as an instrument, we show that a 10 percent increase in drinking establishments is associated with a 4 percent increase in violent crime. Reduced-form estimates suggest that legalizing the sale of alcohol to the general public for on-premises consumption is associated with an 11 percent increase in violent crime.
Keywords: H75; K42; 330; alcohol; liquor licenses; crime